A multicompartment mathematical model based on host immunity for dissecting COVID-19 heterogeneity. Issue 5 (May 2022) - Li, Jianwei; Wu, Jianghua; Zhang, Jingpeng; Tang, Lu; Mei, Heng; Hu, Yu; Li, Fangting
Abstract: The determinants underlying the heterogeneity of coronavirus disease 2019 (COVID-19) remain to be elucidated. To systemically analyze the immunopathogenesis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, we built a multicompartment mathematical model based on immunological principles and typical COVID-19-related characteristics. This model integrated the trafficking of immune cells and cytokines among the secondary lymphoid organs, peripheral blood and lungs. Our results suggested that early-stage lymphopenia was related to lymphocyte chemotaxis, while prolonged lymphopenia in critically ill patients was associated with myeloid-derived suppressor cells. Furthermore, our model predicted that insufficient SARS-CoV-2-specific naïve T/B cell pools and ineffective activation of antigen-presenting cells (APCs) would cause delayed immunity activation, resulting in elevated viral load, low immunoglobulin level, etc. Overall, we provided a comprehensive view of the dynamics of host immunity after SARS-CoV-2 infection that enabled us to understand COVID-19 heterogeneity from systemic perspective. Abstract : COVID-19; Mathematical model; Host immunity; Heterogeneity.